An Economic Model for Bioprospecting Contracts - Paulo A.L.D. Nunes; Helen Ding; Laura Onofri (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper explores the use of a micro-economic model to analyse the provisions and parties of bioprospecting contracts. It focuses on the pharmaceutical industry as the representative biodiversity buyer, presenting an original theoretical framework that explains the main contract characteristics or stylised facts. Against this background, it considers the main contractors involved in these private contracts, i.e. biodiversity sellers and biodiversity buyers, analysing both the magnitude and distribution of the respective payoffs. Particular attention is devoted to the different, mixed impacts of bioprospecting contracts and patenting on social welfare. The positive welfare impacts delivered by bioprospecting contracts are associated with the potential discovery of a new drug product, i.e. productivity gains, non-monetary benefit-sharing or transfers and royalty revenues. The negative welfare impact results from the legal creation of a monopoly and the related well-known effect on the consumer surplus. Finally, the potential redistribution effects are limited, and a potential enforcement of this objective may jeopardise the desirability of the contracts since this action would lead to a significant increase in the transaction costs.
Keywords: D21; D23; D61; L14; Q57; 330; Bioprospecting Contract; Genetic Resource; Biodiversity Buyer; Biodiversity Seller; Patenting; Welfare Analysis; Benefit Sharing; Biodiversität; Vertrag; Pharmazeutische Industrie; Immaterialgüterrechte; Wohlfahrtsanalyse